Severe Shivering as an Adverse Effect of Regadenoson Myocardial Perfusion Imaging - Ahmad, Tanjeev (Cureus, 2021)
Regadenoson myocardial perfusion imaging (MPI) is a widely used screening study for patients with an intermediate pretest probability of coronary artery disease (CAD). Via selective agonism of the adenosine A2A receptor, regadenoson can induce coronary steal, revealing stenotic vessel territory through transient ischemia. Common side effects of this medication include chest pain, shortness of breath, nausea, vomiting, atrioventricular block, seizure, and allergic reactions. Here we present a case of severe shivering and chest tightness after the administration of regadenoson, along with a physiologic explanation and treatment.